2021
DOI: 10.3389/fphar.2021.684976
|View full text |Cite
|
Sign up to set email alerts
|

Patchouli Alcohol Modulates the Pregnancy X Receptor/Toll-like Receptor 4/Nuclear Factor Kappa B Axis to Suppress Osteoclastogenesis

Abstract: The incidence of osteoporosis, which is primarily characterized by plethoric osteoclast (OC) formation and severe bone loss, has increased in recent years. Millions of people worldwide, especially postmenopausal women, suffer from osteoporosis. The drugs commonly used to treat osteoporosis still exist many disadvantages, but natural extracts provide options for the treatment of osteoporosis. Therefore, the identification of cost-effective natural compounds is important. Patchouli alcohol (PA), a natural compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Since the publication of our original paper on microbial metabolites and PXR (Venkatesh, Mukherjee et al 2014), several groups have independently replicated our findings concerning IPA (indole propionic acid) and its effects on mouse intestinal barrier function (Dodd, Spitzer et al 2017); IPA abrogates intestinal inflammation (Konopelski and Mogilnicka 2022); IPA action partly depends on PXR (Pulakazhi Venu, Saifeddine et al 2019, Xiao, Cui et al 2020, Du, Qi et al 2021; PXR inversely regulates TLR4 (Esposito, Nobile et al 2016, Huang, Mukherjee et al 2018, Erickson, Alston et al 2020, Lu, Jiang et al 2021, Su, Zhang et al 2022, Yuan, Lv et al 2022; epithelial TLR4 regulates inflammation and tumors (Fukata, Shang et al 2011, Sodhi, Neal et al 2012, Burgueño, Fritsch et al 2021; discovery of additional indole microbial metabolites (e.g., indole acetamide) with weak effects on PXR (Illés, Krasulová et al 2020). Two reports from the same investigators challenge the notion that epithelial TLR4 is functional (Crame, Bowen et al 2021, Tam, Coller et al 2022; however, further work is needed to clarify this discrepancy as these observations are likely to be context-and model-specific (Gribar, Anand et al 2008, Takahashi, Sugi et al 2009, Soliman, Michelsen et al 2010, Nanthakumar, Meng et al 2011, Sodhi, Neal et al 2012, Li, Teo et al 2014, Belmonte, Achamrah et al 2016, Dheer, Santaolalla et al 2016, Kim, Li et al 2016, Coleman and Haller 2017, Inoue, Yajima et al 2017, Hu, Tan et al 2018, Latorre, ...…”
Section: Brief Historical Perspectivementioning
confidence: 57%
“…Since the publication of our original paper on microbial metabolites and PXR (Venkatesh, Mukherjee et al 2014), several groups have independently replicated our findings concerning IPA (indole propionic acid) and its effects on mouse intestinal barrier function (Dodd, Spitzer et al 2017); IPA abrogates intestinal inflammation (Konopelski and Mogilnicka 2022); IPA action partly depends on PXR (Pulakazhi Venu, Saifeddine et al 2019, Xiao, Cui et al 2020, Du, Qi et al 2021; PXR inversely regulates TLR4 (Esposito, Nobile et al 2016, Huang, Mukherjee et al 2018, Erickson, Alston et al 2020, Lu, Jiang et al 2021, Su, Zhang et al 2022, Yuan, Lv et al 2022; epithelial TLR4 regulates inflammation and tumors (Fukata, Shang et al 2011, Sodhi, Neal et al 2012, Burgueño, Fritsch et al 2021; discovery of additional indole microbial metabolites (e.g., indole acetamide) with weak effects on PXR (Illés, Krasulová et al 2020). Two reports from the same investigators challenge the notion that epithelial TLR4 is functional (Crame, Bowen et al 2021, Tam, Coller et al 2022; however, further work is needed to clarify this discrepancy as these observations are likely to be context-and model-specific (Gribar, Anand et al 2008, Takahashi, Sugi et al 2009, Soliman, Michelsen et al 2010, Nanthakumar, Meng et al 2011, Sodhi, Neal et al 2012, Li, Teo et al 2014, Belmonte, Achamrah et al 2016, Dheer, Santaolalla et al 2016, Kim, Li et al 2016, Coleman and Haller 2017, Inoue, Yajima et al 2017, Hu, Tan et al 2018, Latorre, ...…”
Section: Brief Historical Perspectivementioning
confidence: 57%
“…Lu et al. ( 64 ) demonstrated that PA suppressed osteoclastogenesis by downregulating TLR4/Myd88/TRAF6 via pregnane X receptor (PXR) and inhibited NF-κB signaling. Bacteroides vulgatus is identified to be a probiotic microbiota.…”
Section: Current Treatments For Osteoporosis By Targeting Tlr4mentioning
confidence: 99%
“…TLR4, one of the receptors of LPS, increases in both osteoclast differentiation and survival. Within the topic of this review, three included studies ( 60 , 62 , 64 ) reported the roles of TLR4/TRAF6 in osteoporosis development. He et al.…”
Section: Current Treatments For Osteoporosis By Targeting Tlr4mentioning
confidence: 99%
“…It is suggested that these two TLR play an important role in OC genesis. Lu et al (30) have shown that patchoulol can inhibit OC activity and bone resorption by regulating the expression of TLR4.…”
Section: Toll-like Receptorsmentioning
confidence: 99%